Properties of FeAlSi-X-Y Alloys (X,Y=Ni, Mo) Prepared by Mechanical Alloying and Spark Plasma Sintering - Průša, Filip; Proshchenko, Olga; Školáková, Andrea; Kučera, Vojtěch; Laufek, František (Materials (Basel, Switzerland), 2020)
Short-term mechanical alloying and compaction by spark plasma sintering was used for the production of FeAl20Si20Mo20-XNiX (X corresponds to 5-15 wt %) alloy, which showed an ultrafine-grained microstructure with dimensions of phases around 200 nm or smaller. It was found that the addition of Mo and Ni to the FeAl20Si20 alloy results in the formation of the AlMoSi phase compared to the three-phase FeAl20Si20 alloy, which initially contained FeSi, Fe3Si, and Fe3Al2Si3 phases. All the investigated alloys increased their hardness, reaching up to 1401 HV 1 for the FeAl20Si20Mo5Ni15 alloy, which contained in total 58.5% of the FeSi and Fe3Al2Si3 phases. As a result, all the prepared alloys showed one order magnitude lower wear rates ranging from 3.14 to 5.97·10-6 mm3·N-1·m-1 as well as significantly lower friction coefficients compared to two reference tool steels. The alloys achieved high compressive strengths (up to 2200 MPa); however, they also exhibited high brittleness even after long-term annealing, which reduced the strengths of all the alloys below approximately 1600 MPa. Furthermore, the alloys were showing ductile behavior when compressively tested at elevated temperature of 800 °C. The oxidation resistance of the alloys was superior due to the formation of a compact Al2O3 protective layer that did not delaminate.
Keywords: mechanical alloying; spark plasma sintering; oxidation resistance; wear; hardness; compressive strength